2021
DOI: 10.1111/irv.12915
|View full text |Cite
|
Sign up to set email alerts
|

Early epidemiological investigations: World Health Organization UNITY protocols provide a standardized and timely international investigation framework during the COVID‐19 pandemic

Abstract: Background The declaration of Coronavirus disease 2019 (COVID‐19) as a Public Health Emergency of International Concern (PHEIC) on 30 January 2020 required rapid implementation of early investigations to inform appropriate national and global public health actions. Methods The suite of existing pandemic preparedness generic epidemiological early investigation protocols was rapidly adapted for COVID‐19, branded the ‘UNITY studies’ and promoted globally for the implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 4 publications
0
105
0
1
Order By: Relevance
“…Since 2020, in order to curb the spread of COVID-19, governments around the world have implemented a range of physical distancing and other protective measures recommended by the World Health Organization [ 1 , 2 ]. School closure and suspension of face-to-face teaching was one of the most consistently applied strategies globally to mitigate the pandemic, and this strategy necessitated an abrupt shift from traditional classroom-based instruction to emergency remote teaching [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2020, in order to curb the spread of COVID-19, governments around the world have implemented a range of physical distancing and other protective measures recommended by the World Health Organization [ 1 , 2 ]. School closure and suspension of face-to-face teaching was one of the most consistently applied strategies globally to mitigate the pandemic, and this strategy necessitated an abrupt shift from traditional classroom-based instruction to emergency remote teaching [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of the WHO's HHTI protocol is to gain an early understanding of the transmission dynamics within the household setting 4 . HHTIs are prospective case-ascertained studies that investigate confirmed cases and their household close contacts 5 . Effectively, the household transmission design is a study with two observational components (Figure 1): the identification of eligible COVID-19 cases from a source population (case series), and subsequent recruitment of all their household contacts on the basis of exposure to the primary case of COVID-19 within the household (cohort study).…”
Section: The Household Transmission Designmentioning
confidence: 99%
“…JP Villanueva-Cabezas 1,2 ; Violeta Spirkoska 1,5 , Adrian J Marcato 1,3 ; Niamh Meagher 1,4 ; James E Fielding 1,4,5 ; Isabel Bergeri 6 ; Hannah Lewis 6 ; Marta Valenciano 6,7 ; Richard Pebody 8 ; David J Price 1,4…”
Section: Annexunclassified
See 2 more Smart Citations